1963
DOI: 10.1172/jci104853
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Plasma Acth Concentration With Adrenocortical Response in Normal Human Subjects, Surgical Patients, and Patients With Cushing's Disease*

Abstract: The role of ACTH in various clinical disorders has been difficult to ascertain because the available assay methods have lacked the sensitivity necessary for valid quantitation of the hormone in the plasma of normal subjects (1-4). Even the method of Lipscomb and Nelson (5), the most sensitive practical bioassay procedure now available, usually requires the injection of at least 0.05 mU of ACTH per rat, if responses are to be elicited that will be statistically significant without the use of a prohibitive numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

1966
1966
1976
1976

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(39 citation statements)
references
References 20 publications
2
36
0
1
Order By: Relevance
“…Similar circadian rhythms have also been described for ACTH (3) and plasma renin activity (4). The plasma aldosterone rhythm therefore might he causally related to one or both of these stimuli.…”
Section: Introductionsupporting
confidence: 77%
“…Similar circadian rhythms have also been described for ACTH (3) and plasma renin activity (4). The plasma aldosterone rhythm therefore might he causally related to one or both of these stimuli.…”
Section: Introductionsupporting
confidence: 77%
“…The disagreements in values obtained from small numbers of subjects by different investigators may therefore be more apparent than real. However, the values obtained by Ney et al (31) at 6 a.m. average significantly lower than those obtained even later in the morning by other investigators using the same assay system (28); it is possible that the extraction of the large volumes of plasma by Ney et al (31) was not as efficient as that observed with smaller volumes (30).…”
Section: U Insulin/kgmentioning
confidence: 63%
“…Further¬ more, the relationships with regard to both time of onset and duration of lh release (Niswender, Reichert & Zimmerman, 1970) (Fonzo, Mins & Nelson, 1967). In this context, the first evidence for peak occurrence was at 09.00 hours; a time associated with heightened adrenocorticosteroid secretion in other species (Diraimondo & Forsham, 1956;Ney, Shimizu, Nicholson, Island & Liddle, 1963). Further evidence for adrenal implication was found in the preliminary 218 N.B.…”
Section: Introductionmentioning
confidence: 93%